Supporting digital humanities for knowledge acquisition in modern libraries - Sacco, Kathleen L. 1970-; Richmond, Scott S. 1982-; Parme, Sara 1985-; Wilkes, Kerrie Fergen (Advances in library and information science (ALIS) book series, 2015)
Digital Humanities is a burgeoning field of research and education concerned with the intersection of technology and history, philosophy, linguistics, literature, music, cultural studies, and the arts. Supporting Digital Humanities for Knowledge Acquisition in Modern Libraries aims to stand at the forefront of this emerging discipline, targeting an audience of researchers and academicians, with a special focus on the role of libraries and library staff. In addition to a collection of chapters on crucial issues surrounding the digital humanities, this volume also includes a fascinating account of the painstaking restoration efforts surrounding a 110-year-old handwritten historical source document, the results of which (never before published on this scale) culminate in a full-color, 70-page photographic reproduction of the 1904 Diary of Anna Clift Smith.--Provided by publisher.